The cleaner of Chartres : a novel - Vickers, Salley (Viking, 2012)
Working as a cleaner in the cathedral of Chartres for more than twenty years, Agnès Morel profoundly transforms local lives by performing small tasks and using her subtle influence until an accidental encounter reveals tragic incidents from her youth.